Spirometry filters can be used to detect exhaled respiratory viruses. (26th September 2016) - Mitchell, Alicia B; Mourad, Bassel; Tovey, Euan; Buddle, Lachlan; Peters, Matthew; Morgan, Lucy; Oliver, Brian G
Abstract: Respiratory viruses are very common in the community and contribute to the burden of illness for patients with chronic respiratory diseases, including acute exacerbations. Traditional sampling methods are invasive and problematic to repeat. Accordingly, we explored whether respiratory viruses could be isolated from disposable spirometry filters and whether detection of viruses in this context represented presence in the upper or lower respiratory tract. Discovery ( n   =  53) and validation ( n   =  49) cohorts were recruited from a hospital outpatient department during two different time periods. Spirometry mouthpiece filters were collected from all participants. Respiratory secretions were sampled from the upper and lower respiratory tract by nasal washing (NW), sputum, and bronchoalveolar lavage (BAL). All samples were examined using RT-PCR to identify a panel of respiratory viruses (rhinovirus, respiratory syncytial virus, influenza A, influenza B, parainfluenza virus 1, 2 & 3, and human metapneumovirus). Rhinovirus was quantified using qPCR. Paired filter-NW samples ( n   =  29), filter-sputum samples ( n   =  24), filter-BAL samples ( n   =  39) and filter-NW-BAL samples ( n   =  10) provided a range of comparisons. At least one virus was detected in any sample in 85% of participants in the discovery cohort versus 45% in the validation cohort. Overall, 72% of viruses identified in the paired comparator method matched those detected in spirometry filters. There was a high correlation between viruses identified in spirometry filters compared with viruses identified in both the upper and lower respiratory tract using traditional sampling methods. Our results suggest that examination of spirometry filters may be a novel and inexpensive sampling method for the presence of respiratory viruses in exhaled breath.